Treatment with metformin and a dipeptidyl peptidase-4 inhibitor elevates apelin levels in patients with type 2 diabetes mellitus - Fan YJ; Zhang Y; Li XS; Zheng H; Song YP; Zhang N; Shen CF; Fan XF; Ren FD; Shen JY; Ren GG; Yang JL (Dove Medical Press, 2015)
Yujuan Fan,* Yu Zhang,* Xuesong Li,* Hui Zheng, Yuping Song, Ning Zhang, Chunfang Shen, Xiaofang Fan, Fengdong Ren, Jiayi Shen, Guoguang Ren, Jialin Yang Department of Endocrinology, Central Hospital of Minhang District, Minhang Hospital affiliated to Fudan University, Shanghai, People’s Republic of China *These authors contributed equally to this work Background: The objective of this study was to assess the effects of metformin monotherapy or combined treatment with a dipeptidyl peptidase-4 inhibitor (vildagliptin) on apelin levels in patients with type 2 diabetes mellitus. Methods: Twenty-five patients with poor glycemic control (glycosylated hemoglobin >6.5% [48 mmol/mol]) taking 1,000 mg of metformin daily and 25 healthy controls matched for age and body mass index were enrolled in this study. Anthropometric parameters, glycemic and lipid profile, insulin resistance (homeostasis model assessment of insulin resistance index), and apelin levels were measured at baseline and at 12-week and 24-week visits. Results: At baseline, apelin levels were higher in the T2DM patients than in the controls (1.93±1.81 ng/mL versus 6.09±4.90 ng/mL; P<0.05). After 12 weeks, when vildagliptin was added, fasting blood glucose and glycosylated hemoglobin decreased, and apelin levels increased further (from 6.09±4.90 ng/mL to 24.23±12.59 ng/mL; P<0.05). Follow-up at 24 weeks showed no further improvement in the glycemic profile and no further increase in apelin levels. Conclusion: Both metformin and vildagliptin favorably changed glycemic indices and apelin levels. For patients inadequately controlled on a low dose of metformin, addition of vildagliptin may be helpful. Keywords: glucagon-like peptides, glucose-dependent insulinotropic polypeptide, antidiabetic drug, adipocytokine